A proposal for analyzing the inflammatory and remodeling processes of mucosa in chronic rhinosinusitis with nasal polyposis through MRI - Débora de Carvalho Garcez; Miguel Soares Tepedino; Debora Petrungaro Migueis; Pedro Miño Vianna; Andrea Santos Dumont Costacurta; Elyzabeth Avvad Portari; Alexandre Malta da Costa Messeder; Richard Louis Voegels; Alexandre Coelho Boggi; Reginaldo Raimundo Fujita; Andrew Thamboo; Rogério Pezato (Brazilian Journal of Otorhinolaryngology)
Objectives: Chronic Rhinosinusitis with Nasal Polyposis (CRSwNP) is a disease characterized by chronic inflammation and tissue remodeling process. The remodeling process in nasal polyps has mainly been studied by histology analysis. However, it is limited to a polyp fragment and requires tissue removal. The present study aims to evaluate the ability of Magnetic Resonance Imaging (MRI) to depict and characterize the remodeling process in patients with CRSwNP. Methods: 30 patients that met clinical diagnostic criteria for CRSwNP, without previous history of rhinosinusitis surgery were submitted to MRI scan (conventional, diffusion-weighted and DCE MRI) and compared with polyp tissue histological findings, IL-6 concentrations in the tissue and eosinophil count in the blood. The examinations were evaluated, independently, by two radiologists blinded to other radiological and histological data. The pathologist, blinded to MRI results, also compared the tissue sample from the most central and the most peripheral portion of the polypoid tissue adjacent to the floor of the nasal fossa. Results: This study demonstrated a characteristic pattern of nasal polyps, whose peripheral portions of nasal polypoid tissue are edematous, whereas the central portions in the middle meatus and in the middle and upper ethmoid are predominantly fibrotic. ADC values found in the most anterior portion of the polyps may be a marker for radiological phenotyping the remodeling process. This non-invasive analysis presented a high degree of agreement in the fibrosis and edema rating by two radiologists and the histological analysis was concordant with the MRI findings. The polyps were characterized as eosinophilic, and no relationship was found between the severity of the eosinophilic inflammatory process or concentration of IL-6 and the remodeling process. Conclusion: MRI by using T2-weighted imaging sequence and ADCs values allows tissue characterization and is an effective tool for the differentiation of edematous and fibrotic components in CRSwNP. Level of evidence: 3.